2015
DOI: 10.1093/database/bav069
|View full text |Cite
|
Sign up to set email alerts
|

OCDB: a database collecting genes, miRNAs and drugs for obsessive-compulsive disorder

Abstract: Obsessive-compulsive disorder (OCD) is a psychiatric condition characterized by intrusive and unwilling thoughts (obsessions) giving rise to anxiety. The patients feel obliged to perform a behavior (compulsions) induced by the obsessions. The World Health Organization ranks OCD as one of the 10 most disabling medical conditions. In the class of Anxiety Disorders, OCD is a pathology that shows an hereditary component. Consequently, an online resource collecting and integrating scientific discoveries and genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…Dysregulations in the major stress systems (cortico–strial–thalamic–cortical circuits and inflammatory functions) have been demonstrated in OCD and these could be contributing to increased oxidative stress. Oxidative stress is closely related to the inflammatory pathway in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulations in the major stress systems (cortico–strial–thalamic–cortical circuits and inflammatory functions) have been demonstrated in OCD and these could be contributing to increased oxidative stress. Oxidative stress is closely related to the inflammatory pathway in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Several tools have also been developed to directly link miRNAs to biological processes such as DMirNet [188], miRnet [110] and DIANA-miRPath v3.0 [107]. Many tools and resources have also been developed to link miRNAs to speciic phenotypes/environments including diseases such as miRNAs in obsessive-compulsive disorder [189], autophagy in gerontology [190], epilepsy [191] and cancer [192]. Among the most popular integrated tools, DIANA-tools (www.microrna.gr) covers a wide scope and research scenarios integrating several tools such as DIANA-microT-CDS, DIANA-TarBase v7.0, DIANA-miRGen v3.0, DIANA-miRPath v3.0, and DIANA-mirExTra v2.0.…”
Section: Integrated Tools For Mirna Analysismentioning
confidence: 99%
“…[1] The WHO has ranked it as one of the 10 debilitating medical conditions. [2] The main symptoms of this disease are obsession and compulsion, which involves unwanted and disturbing thoughts, ideas or sensations. The OCD is the result of the usual concerns about the problems of life in which a person considers them to be the result of his own mind.…”
Section: Introductionmentioning
confidence: 99%